Assessment and Improvement of Melt Quality of Recycled Secondary A357 Alloy by Application of the High Shear Melt Conditioning (HSMC) Technology - Zhichao Niu; Zhongping Que; Jayesh B. Patel; Zhongyun Fan (Crystals)
In addition to impurities in recycled aluminum alloys, non-metallic inclusions are a significant factor that deteriorates the material’s castability and final mechanical properties. This, therefore, restricts the ability to transition from a primary to secondary aluminum alloy. In this study, the cleanliness of the recycled A357 alloy was evaluated through non-metallic inclusions’ characterization, hydrogen content measurement, fluidity test, and casting defects identification. The non-metallic inclusions generated during the recycling process of A357 alloy were collected by the pressurized melt filtration technique. All of the inclusion types collected during filtration were examined and identified by analytical scanning electron microscopy (SEM). Extra additions of up to 2 wt.% swarf in these secondary A357 alloys were designed to simulate highly contaminated alloys. Different to the conventional melt cleaning technologies that mainly focus on complete removal of inclusions, this study developed a novel approach that combines the removal of easily removeable inclusions while preserving well-dispersed inclusions that do not adversely affect the mechanical properties. This study demonstrates that high shear melt conditioning (HSMC) technology can achieve well-dispersed small non-metallic inclusions, low hydrogen content, improved fluidity, and fewer casting defects. As a result, the melt quality of the recycled A357 alloys has achieved a quality comparable to that of primary A357 alloy.